INTEGRATION OF DIGITAL-BASED BANKING SERVICES ON CUSTOMER SATISFACTION (STUDY OF INDONESIAN ISLAMIC BANKS) KCP KOTA PINANG) - Mawantika, Fadila (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
The performance of Islamic banking in Indonesia and its branches in various regions on the economic growth of a country cannot be underestimated by anyone, as well as the existence of Islamic banking in global economic growth has received the highest recognition by various world economies. The purpose of this study is still about the factors of digitalization of Islamic banking, banking services, trust and banking innovation and their influence on customer satisfaction. The population in the study were customers of Bank Syariah Indonesia Labuhanbatu Selatan Regency registered in December 2022 totaling 18,203 people. The sampling technique refers to the minimum sample size in PLS-SEM is 30-100 sample sizes, so the author determines to use a sample of 100 people. The sample withdrawal technique chose purposive sampling technique, as for the consideration in the research of customers who saved for approximately 6 months. Data collection techniques using questionnaires (google form), interviews and written or primary data. The author's data analysis technique uses SmartPLS 4.0 to prove each partial direct effect between the independent variable and the dependent variable. The results of this study 1) Islamic bank digitalization variables partially affect banking innovation, 2) Islamic bank digitalization variables partially affect customer satisfaction, 3) banking innovation variables partially affect customer satisfaction, 4) banking service variables partially affect banking innovation, 5) banking service variables partially affect customer satisfaction, 6) trust variables partially affect banking innovation and 7) trust variables partially have no positive and insignificant effect on customer satisfaction